2004
DOI: 10.1128/iai.72.9.5159-5167.2004
|View full text |Cite
|
Sign up to set email alerts
|

Proteus mirabilis ZapA Metalloprotease Degrades a Broad Spectrum of Substrates, Including Antimicrobial Peptides

Abstract: The 54-kDa extracellular metalloprotease ZapA is an important virulence factor of uropathogenic Proteus mirabilis. While ZapA has the ability to degrade host immunoglobulins (Igs), the dramatic attenuation of virulence in ZapA mutants suggests that this enzyme may have a broader spectrum of activity. This hypothesis was tested by in vitro assays with purified ZapA and an array of purified protein or peptide substrates. The data reveal that many proteins found in the urinary tract are substrates of ZapA proteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
138
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 26 publications
1
138
0
Order By: Relevance
“…Fewer studies have examined the activity of bacterial proteases against other antimicrobial peptides but Pr. mirabilis ZapA has been shown to degrade hbD-1 (Belas et al, 2004) and LasB has been shown to cleave SLPI (Sponer et al, 1991). Our studies have shown that at least one of the B. cenocepacia ZmpA and ZmpB proteases had activity against hbD-1, LL-37, elafin and SLPI.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Fewer studies have examined the activity of bacterial proteases against other antimicrobial peptides but Pr. mirabilis ZapA has been shown to degrade hbD-1 (Belas et al, 2004) and LasB has been shown to cleave SLPI (Sponer et al, 1991). Our studies have shown that at least one of the B. cenocepacia ZmpA and ZmpB proteases had activity against hbD-1, LL-37, elafin and SLPI.…”
Section: Discussionmentioning
confidence: 67%
“…Many proteases have been reported to degrade LL-37, including Proteus mirabilis ZapA (Belas et al, 2004), Staphlylococcus aureus aureolysin (SieprawskaLupa et al, 2004), Ps. aeruginosa LasB, Enterococcus faecalis gelatinase, Streptococcus pyogenes SpeB (Schmidtchen et al, 2002), and a Bacillus anthracis metalloprotease (Thwaite et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The substrate specificity of ZapA had been characterized using fluorescent peptides derived from bioactive peptides and the oxidized β-chain of insulin. As one of the most important virulence factors of P. mirabilis, the role of ZapA in pathogenesis was probably due to the destruction of IgA, antimicrobial peptides, bioactive molecules, and structural components of the host cells (Fernandes et al 2000;Anéas et al 2001;Belas et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Metalloprotease ZapA from P. mirabilis degrades a broad spectrum of substrates, including IgA and antimicrobial peptides (Loomes et al 1990;Almogren et al 2003;Belas et al 2004). The substrate specificity of ZapA had been characterized using fluorescent peptides derived from bioactive peptides and the oxidized β-chain of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…These metalloproteases are members of the thermolysin and serralysin families respectively. It has been demonstrated that each of these bacterial proteases functions as a virulence factor during the process of infection, each having a deleterious effect on the host including the degradation of a broad range of host tissue proteins, and biomolecules involved in innate immunity such as immunoglobulins, complement factors, antimicrobial peptides and cytokines [7][8][9][10][11][12]. In addition, LasB acts within the bacterial cell as a regulator of polysaccharide (alginate) secretion [13].…”
Section: Introductionmentioning
confidence: 99%